GAMBARAN SENSITIVITAS DAN SPESIFISITAS UJI RAPID DIAGNOSTIC TEST DENGAN PEMERIKSAAN MIKROSKOPIS APUSAN DARAH TEPI SEBAGAI GOLD STANDARD PEMERIKSAAN MALARIA DI RUMAH SAKIT DR. HARDJANTO BALIKPAPAN - wafiq Azizah; Dwi Haryatmi (Klinikal Sains : Jurnal Analis Kesehatan, 2025)
Malaria is a disease caused by the Plasmodium parasite and transmitted through the bite of an infected female Anopheles mosquito. Accurate diagnosis is essential for effective malaria management, especially in endemic areas such as East Kalimantan. This study aims to evaluate the sensitivity and specificity levels of the Rapid Diagnostic Test (RDT) in detecting malaria, correlating the results with thin blood smear microscopy, which serves as the gold standard at Dr. Hardjanto Hospital in Balikpapan. A cross-sectional approach was used, involving 30 samples from patients suspected of having malaria. The analysis showed that RDT had a sensitivity of 86.67% and a specificity of 93.33%, with a positive predictive value (PPV) of 92.85% and a negative predictive value (NPV) of 87.56%. The conclusion of this study is that the specificity of the Rapid Diagnostic Test (RDT) met the minimum criteria set by the World Health Organization (WHO), which is greater than 90%, with a result of 93.33%. However, the sensitivity level was still below the WHO's recommended standard of ≥95%, as it was found to be 86.67% in this study